A little more conversation - The influence of communicative context on syntactic priming in brain and behavior - Schoot, Lotte; Menenti, Laura; Hagoort, Peter; Segaert, Katrien (Frontiers in Psychology, 2014)
We report on an fMRI syntactic priming experiment in which we measure brain activity for participants who communicate with another participant outside the scanner. We investigated whether syntactic processing during overt language production and comprehension is influenced by having a (shared) goal to communicate. Although theory suggests this is true, the nature of this influence remains unclear. Two hypotheses are tested: i. syntactic priming effects (fMRI and RT) are stronger for participants in the communicative context than for participants doing the same experiment in a non-communicative context, and ii. syntactic priming magnitude (RT) is correlated with the syntactic priming magnitude of the speaker’s communicative partner. Results showed that across conditions, participants were faster to produce sentences with repeated syntax, relative to novel syntax. This behavioral result converged with the fMRI data: we found repetition suppression effects in the left insula extending into left inferior frontal gyrus (BA 47/45), left middle temporal gyrus (BA 21), left inferior parietal cortex (BA 40), left precentral gyrus (BA 6), bilateral precuneus (BA 7), bilateral supplementary motor cortex (BA 32/8) and right insula (BA 47). We did not find support for the first hypothesis: having a communicative intention does not increase the magnitude of syntactic priming effects (either in the brain or in behavior) per se. We did find support for the second hypothesis: if speaker A is strongly/weakly primed by speaker B, then speaker B is primed by speaker A to a similar extent. We conclude that syntactic processing is influenced by being in a communicative context, and that the nature of this influence is bi-directional: speakers are influenced by each other.